Logistics in Yemen: Identifying Demerits on Lack of Railways in Yemen - Najeeb, Hisham; Raju, Valliappan; Rahman, Shafiqur (International Journal of Supply Chain Management, 2019)
If one asks today whether Yemen can be extended by railway lines, it is natural to answer that the geographical nature of Yemen does not allow the extension of the railway line. It is surprising that the Ottoman Empire decided more than 100 years ago to complete this project, but the fall of the empire deprived Yemenis of this Great achievement. Under the title of establishing a modern network of railways for metals, goods and passengers, in recent years, practical steps have been taken to establish a railway network in Yemen and linking it to an international network of economic feasibility studies, but the railway project in Yemen is still just studies prepared by several companies. In 2013 there were talks between the Yemeni government and Russia, the outcome of the Yemeni-Russian talks committee was for the planning of the establishment of a local company in Yemen specializing in railways Under the supervision of the Russian leadership, a project that is the first of its kind as it aims to build an infrastructure. In this research paper the author attempt to use quantitative and qualitative research method, plan and execute fieldwork, collecting data from Competent ministerial bodies, ministry of transportation, Visit the specified area of the project) mineral wealth areas, coastal areas) etc. in Yemen, during fieldwork. Compile preliminary maps of the first alternative - Shahn / Aden and the second alternative - Muscat / Salalah / Sarfeet / Algheiza / Aden. During fieldwork and data collection, the author will visit ministry of transportation to meet the representative to get the requested data of the Proposed railway project along with Yemen land transportation affairs authority, then the author will visit designated area of the proposed project to meet the local authorities of each area to collect the data and discussing the main causes of the project's failure and delay along with that inspecting the security and services of the project’s designated area, although the government has conducted several studies on this project. After that the author will visit a the Minister of Transportation or a senior figure from the ministry for an interview to discuss the main challenges and constraints that causes the failure of the project and the delay to support the study, finally the author will visit Ministry of Public works and roads to collect preliminary maps of the International Coastal Railway (from Haradh to Shahn) and the economic feasibility study of the railway linking the mineral wealth areas (Al-Jouf and Marib Shabwa Balahaf). After analysing data and identifying findings that led to the projects failure, the author found three main challenges at present to build the railway project in Yemen are the absence of government economy, security and political stability.